Olfactory Function and Quality of Life Following Microscopic Endonasal Transsphenoidal Pituitary Surgery. Issue 4 (January 2015) - Wang, Shousen; Chen, Yehuang; Li, Jianzhong; Wei, Liangfeng; Wang, Rumi; Lin., Yung-Song
<x xml:space="preserve">Abstract</x> Abstract Olfactory outcomes as well as oronasal postoperative complications of transsphenoidal pituitary surgery have not been well studied. The objective of this study was to investigate nasal symptoms including olfactory function as well as quality of life following transsphenoidal pituitary surgery. The study is designed as a prospective cohort study set in a single tertiary hospital. A total of 53 patients with pituitary adenomas were included. All patients underwent pituitary surgery with the right-sided endonasal transsphenoidal approach. Outcomes were assessed with the Chinese version of the Medical Outcomes Study Short Form-36 (SF-36) to survey patient health, the Chinese version of the 22-item Sinonasal Outcome Test (SNOT-22), and a Toyota and Takagi (T&T) olfactometer. Assessments were carried out before surgery and at 1 week, and 1 and 4 months after surgery. The overall SF-36 scores were significantly lower, but the SNOT-22 scores were higher at 1 week and 1 month postoperatively compared with baseline (all P < 0.001). The results of T&T olfactometer testing showed that there was a significant decline in the ability to detect odors postoperatively, even at 4 months. Multivariate linear regression analysis showed that lower education level, partial tumor removal, and longer duration of surgery were independent risk factors for a higher SNOT-22 score at 1 week after surgery. The findings show that microscopic endonasal transsphenoidal pituitary surgery impairs olfactory function in most patients for at least 4 months after surgery.